Balinese Folktales As A Medium: Modifying Stories Of The Special Need Concept To An Early Age Children - Luh Ayu Tirtayani; I.G.A.A. Wulandari; Lucky Ade Sessiani (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2019)
This article aimed at exploring more deeply the efforts made by teachers of early childhood education in introducing concepts of children with special needs. This article investigated the teachers’ creativity in introducing concepts containing local values to children with special needs, which can support inclusive education. This study used an exploratory research model, with the aim of obtaining explanations of the relationships of case causality. The study was conducted to the teachers on early childhood education in Denpasar Bali. The subjects were determined by verifying the early childhood education institutions which had children with special needs first and this ended up with the involvement of 13 teachers from 10 early childhood education institutions in Denpasar. The data were collected through observation, directed individual and group interviews. The data were analyzed qualitatively by modifying Miles and Huberman’s interactive model. The result showed that the teachers have introduced some types and characteristics of children with special needs by using tales as media and have creatively modified Balinese folktales to fit the needs.